The crazy economics of air freight - Jack Eaton (Intereconomics, 1994)
Measured by value of goods transported, about one third of all international trade today is moved by air. Severe cyclical fluctuations around the generally strong growth trend of the last decade have meant considerable problems for air freight companies, however. How have they attempted to deal with these problems? How would they be advised to behave in future?
Keywords: 330; Aviation